2019
DOI: 10.1371/journal.pone.0212639
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas promotes the adventitious rooting in cucumber under cadmium stress

Abstract: Hydrogen gas (H 2 ) plays an important role in plant development and stress responses. Here, cucumber ( Cucumis sativus L.) explants were used to investigate the roles of H 2 in adventitious root development under cadmium (Cd) stress and its physiological mechanism. The results showed that hydrogen-rich water (HRW) promoted adventitious rooting under Cd stress and 50% HRW obtained the maximal biological response. Compared with Cd treatment, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…We adapted a method from Wang et al (2019) for measuring the malondialdehyde (MDA) content. Leaves of ice plants were harvested before and after salt treatment, and then ground to a fine powder in liquid nitrogen.…”
Section: Malondialdehyde Content Measurementmentioning
confidence: 99%
“…We adapted a method from Wang et al (2019) for measuring the malondialdehyde (MDA) content. Leaves of ice plants were harvested before and after salt treatment, and then ground to a fine powder in liquid nitrogen.…”
Section: Malondialdehyde Content Measurementmentioning
confidence: 99%
“…HRW + Cd treatment also significantly increased in the activity and related gene expressions of APX , DHAR , monodehydroascorbate reductase ( MDHAR ), and GR . Additionally, HRW + Cd treatment increased the contents of osmotic adjustment substances, as well as the activities of POD and PPO, while significantly decreasing IAAO activity [34]. These results confirm that H 2 induces adventitious rooting under Cd stress by decreasing the oxidative damage, increasing osmotic adjustment substance content, and regulating rooting-related enzyme activity.…”
Section: Functions Of Small-molecule Compounds During Adventitiousmentioning
confidence: 61%
“…Also, exogenous H 2 dramatically increased leaf chlorophyll content, Fv/Fm, ɸPSII, and qP as well as the activities of SOD, POD, CAT, and APX enzymes during drought [18]. Additionally, a recent study showed that under cadmium (Cd) stress, 50% HRW was the most proper dose to trigger adventitious rooting in cucumber [34]. Compared with Cd treatment, HRW + Cd treatment significantly reduced the content of malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), superoxide radical (O 2 − ), thiobarbituric acid reactive substances (TBARS), ascorbic acid (AsA), and reduced glutathione (GSH), as well as relative electrical conductivity (REC), lipoxygenase (LOX) activity, AsA/docosahexaenoic acid (DHA) ratio, and GSH/oxidized glutathione (GSSG) ratio, while increasing DHA and GSSG content.…”
Section: Functions Of Small-molecule Compounds During Adventitiousmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified H 2 gas (99.99%, v/v) generated from a hydrogen gas generator (QL-300, Saikesaisi Hydrogen Energy Co., Ltd, Shandong, China) was bubbled into 1000 mL distilled water solution at a rate of 330 mL min −1 for 60 min. Then, the corresponding hydrogen-rich water (HRW) was rapidly diluted to the different saturations required (1, 10, 50 and 100%, [v/v]) (Wang et al 2019a ). The dissolved hydrogen portable meter was used to analyze the H 2 concentration in freshly prepared HRW, and it was maintained at an effective concentration level at 25 °C for at least 12 h (Figs.…”
Section: Methodsmentioning
confidence: 99%